Experience of interinstitutional interaction while delivering of surgical aid in the disasters environment - G. G. Roshchin; Ya. M. Susak; I. J. Slychko; O. V. Mazurenko; N. I. Iskra; V. Yu. Kuzmin (Клінічна хірургія)
Objective. Investigation of interinstitutional interaction environment while delivering of surgical aid in conditions of disaster, the need in certain kinds of surgical operations estimation of efficacy of civil-military interaction in sector of the antiterrorist operation conduction.